2018
DOI: 10.1001/jamasurg.2017.6117
|View full text |Cite
|
Sign up to set email alerts
|

Association of Faculty Entrustment With Resident Autonomy in the Operating Room

Abstract: Faculty entrustment behaviors may be the primary drivers of resident entrustability. Faculty entrustment is a feature of faculty surgeons' teaching style and could be amenable to faculty development efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 30 publications
(75 reference statements)
1
49
1
Order By: Relevance
“…Cases conducted by PGY 3 residents included 36% female cases and 10% male cases, and cases conducted by PGY 5 residents included 34% males and 7% females. It is important to note that in our previous work, postgraduate year was found to be statistically associated with resident entrustability; 19 the means of PGY entrustability scores in that study ranged from 1.31 (PGY 1) to 3.21 (PGY 6). Faculty experience differed by resident sex ( P < .005).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Cases conducted by PGY 3 residents included 36% female cases and 10% male cases, and cases conducted by PGY 5 residents included 34% males and 7% females. It is important to note that in our previous work, postgraduate year was found to be statistically associated with resident entrustability; 19 the means of PGY entrustability scores in that study ranged from 1.31 (PGY 1) to 3.21 (PGY 6). Faculty experience differed by resident sex ( P < .005).…”
Section: Resultsmentioning
confidence: 60%
“…Interestingly, our previous work suggested that faculty experience was not associated with resident entrustability. 19 Independent sample t -tests did not detect a difference in faculty entrustment scores by resident sex (female = 2.54 vs male = 2.35, P = .117). The analysis of same-sex versus intersex faculty/resident case pairings revealed similar results (female = 2.34 vs male = 2.53, P = .10).…”
Section: Resultsmentioning
confidence: 81%
“…A growing concern in current medical education is a lack of trainee autonomy during operative procedures 1 , 3 , 4 , 10 , 18 - 22 . Previously, a discordance has been demonstrated in certain disciplines between residents and attendings regarding resident competency and autonomy 2 , 6 , 13 , 20 , 21 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In order for orthopaedic attendings to better promote resident autonomy, it is critical that they can accurately assess resident competence to allow safe entrustment 9 , 26 - 28 . Several general surgery studies enumerate common factors affecting faculty entrustment: resident competence, resident familiarity, PGY-level, and attending experience 18 , 19 , 27 , 29 , 30 . Given attending perception of resident competence is subjective and susceptible to bias based on resident familiarity and PGY-level, it is important that more objective measures of competence in orthopaedics are implemented 11 , 26 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…1 As a result, all faculty and residents strive to provide the appropriate amount of autonomy and entrustment. [2][3][4][5][6][7][8][9][10] Though there are many articles on clinical teaching where there is implicit information on autonomy and learners, 11 and Carbo provides a toolkit to teach learners autonomy, 12 little is published that provides explicit strategies for assessing learner readiness for independent practice and supporting resident autonomy. 13 Family medicine residents are expected to progressively develop the ability to independently care for patients over the course of their 3-year residency.…”
Section: Introductionmentioning
confidence: 99%